The relationship between cardiorespiratory and accelerometer-derived measures in trail running and the influence of sensor location - Staunton, C. A.; Swarén, M.; Stöggl, T.; Born, D. P.; Björklund, G. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To examine the relationship between cardiorespiratory and accelerometer-derived measures of exercise during trail running and determine the influence of accelerometer location.